This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: y = f ( x ) is a function, (i.e. y = f ( x ) has an inverse function), then; ( 29 ( 29 x x f f =1 AND ( 29 ( 29 x x f f =1 e.g. ( 29 2 2 x f x x= + 2 2 2 2 x y y x x y= ⇒ = + + ( 29 ( 29 2 2 2 2 1 2 2 2 2 1 y x y xy x y x y x x y x + =+ == + =( 29 ( 29 1 2 2 2 2 2 1 2 x x f f x x x + ÷ + =  ÷ + 2 4 2 4 2 2 4 4 x x x x x x + + = +  + = = ( 29 ( 29 1 2 2 2 1 2 2 2 1 x x f f x x x+  ÷ = + + ÷ 2 2 2 2 2 2 2 2 4 4 x x x x x x +  + = + + = = ( ii ) Draw the inverse relation y x Exercise 2H; 1aceg, 2, 3bdf, 5ac, 6bd, 7ac, 9bde, 10adfhj...
View
Full Document
 Spring '11
 dfsfddsf
 Inverse function, Injective function, Inverse relation

Click to edit the document details